Pengaruh Religiusitas, Motivasi, dan Tingkat Literasi Pasar Modal Syariah Terhadap Minat Berinvestasi Pasar Modal Syariah - Muhammad Zainal Abrori; Muhammad Hifdil Islam; Nuruddin Armanto (Prodi Manajemen Universitas Pamulang, 2023)
This study aims to determine the influence of religiosity, motivation, and literacy of the Islamic capital market partially and simultaneously on the investing interest in the Islamic capital market of ISP members in Probolinggo. This study used multiple regression analysis techniques titled